Decay and dephasing of image-potential states due to surface defects and disorder - Weinelt, Martin; Reuss, Christian; Kutschera, Michael; Thomann, Ulrich; Shumay, Igor; Fauster, Thomas; Höfer, Ulrich; Theilmann, Florian; Goldmann, Albrecht (Applied Physics B-Lasers and Optics, 1999)
The dynamics of electrons in image-potential states has been studied by means of time- and energy-resolved two-photon photoemission. The loss of coherence in quantum-beat spectroscopy shows directly the influence of pure dephasing which can be determined also from the difference between the results of linewidth and decay rate measurements. We present several examples for the correlation of decay and dephasing with surface defects and disorder.